2015
DOI: 10.1002/0471142735.im1437s110
|View full text |Cite
|
Sign up to set email alerts
|

Models to Study NK Cell Biology and Possible Clinical Application

Abstract: Natural killer (NK) cells are large granular lymphocytes of the innate immune system, responsible for direct targeting and killing of both virally infected and transformed cells. NK cells rapidly recognize and respond to abnormal cells in the absence of prior sensitization due to their wide array of germline-encoded inhibitory and activating receptors, which differs from the receptor diversity found in B and T lymphocytes resulting from the use of recombination-activation gene (RAG) enzymes. Although NK cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…(43) However, an evolving picture of NK cells is emerging highlighted by diverse subsets with different physiology and effector functions including cytotoxicity, cytokine production, and immune-editing(44). Key studies have demonstrated that NK cells are significantly more complex and more heterogeneous than the classic view of NK cells suggests (45).…”
Section: Bodymentioning
confidence: 99%
See 1 more Smart Citation
“…(43) However, an evolving picture of NK cells is emerging highlighted by diverse subsets with different physiology and effector functions including cytotoxicity, cytokine production, and immune-editing(44). Key studies have demonstrated that NK cells are significantly more complex and more heterogeneous than the classic view of NK cells suggests (45).…”
Section: Bodymentioning
confidence: 99%
“…Due to their localization in lymph nodes combined with their high cytokine production, a growing consensus is emerging that CD56 bright cells function as immune regulators, for example by modulating dendritic cell antigen presentation and by priming T cells toward a Th1 phenotype. (43)…”
Section: Bodymentioning
confidence: 99%
“…Like NK cells, activated NKT cells release in the extracellular compartment pro- and anti-inflammatory cytokines/chemokines with the function of regulating the immune response ( 8 ). The activation of NK and NKT cells derives from the balance of signals coming from activatory and inhibitory receptors ( 9 , 10 ). There are some evidences about the possible involvement of NK and NKT cells in the pathogenesis of BD, but there is a discrepancy in the data.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies by the same group found this was in fact due to activated T cells expressing ASGM1 (23). Even NK1.1, a marker commonly used to deplete NK cells that is more specific, is expressed on other cell types (2). To label an agent as NK specific in mice has always been problematic, particularly in the case in which T cells can be affected, and necessitates the need for T cell-deficient mice and/or adoptive transfer studies using purified NK cells.…”
Section: Involvement Of Pd-1 Pathway and Nk Cells In Cancermentioning
confidence: 99%